2009
DOI: 10.1055/s-0028-1109312
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Keratic Precipitates in Fuchs Heterochromic Uveitis Syndrome

Abstract: KP in FHUS cause a focal damage of endothelial cells reflected in a decreased percentage of healthy hexagonal cells. The degree of endothelial cell damage seems to be low as it does not lead to a significant reduction in the endothelial cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The KP observed in FUS has also been studied in prior studies. 6,8,9,11 Labbé et al 9 reported their IVCM findings 9 The KP observed in that study was reported to be in dendritic shape with a small central body and numerous pseudopodia with accompanying smaller sized dendritic and stippled precipitates. No distinction between primary and secondary KP was made in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The KP observed in FUS has also been studied in prior studies. 6,8,9,11 Labbé et al 9 reported their IVCM findings 9 The KP observed in that study was reported to be in dendritic shape with a small central body and numerous pseudopodia with accompanying smaller sized dendritic and stippled precipitates. No distinction between primary and secondary KP was made in that study.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a series of eight patients with the diagnosis of FUS, Hasler et al 6 demonstrated a lower percentage of hexagonal endothelial cells; in the same study, the decrease in endothelial cell densities of FUS patients was found too small to be significantly different. 6 The current study has the highest number of patients with FUS (n ¼ 36) enrolled for endothelial cell density evaluation. In this regard, the results of our study and those of Brooks et al 17 suggest that chronic low-grade inflammation and KP have detrimental effects on endothelial cell morphology in FUS with currently unknown implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation